Prophets of zoom. (Economist, 2012)
The article discusses the development of a zoomable user interface (ZUI) presentation software program by software company Prezi, focusing on its innovative unlimited canvas, as well as the ability of the presenter to pan, rotate, and zoom during a slideshow. A timeline presentation software program entitled ChronoZoom is also mentioned.